Voices from the ground: The emotional labour of English teachers' work - Loh, Chin Ee; Liew, Warren Mark (Teaching and teacher education, 2016)
This paper examines the complex emotional work of English language teaching in Singapore secondary schools. Findings revealed the emotional burdens, tensions, and challenges associated with the teaching of English, largely attributed to the subject's value-laden content, the stresses of grading student essays, the performance pressures of high-stakes testing, and the need for culturally responsive pedagogies. Further studies of teachers' lived experiences in relation to their disciplinary domains can offer teacher educators and policymakers insights into the ways in which curriculum and policy impact on, and are impacted by, the emotional realities of teachers' work. •The emotions of teaching are experienced in discipline-specific ways.•Study of lived experiences of English teachers' emotional labour in Singapore.•English teachers' lived experiences provide insight to situated, complex practice.•Policy and localized practice should consider discipline-specific emotional labour.